Perception of family planning utilization among type 2 diabetes mellitus women, spouse and health care providers-a qualitative study / Santhi Subramaniam - Santhi , Subramaniam (2019)
Family planning is an effective intervention for reducing pregnancy-related complications and morbidity among women of reproductive age who have type 2 diabetes mellitus (T2DM). Primary healthcare facilities promote family planning services and cater for T2DM women. However, utilization of the family planning methods offered by primary healthcare facilities is reported to be low among T2DM women. Understanding this underutilization of family planning methods and services is critical for pregnancy and disease management optimization. Therefore the main aim of this study is to explore the factors influencing family planning utilization among T2DM women from the perspectives of T2DM women, their spouses and primary healthcare providers in Gombak district, Selangor, Malaysia. This study took place in seven primary healthcare clinics from March to October 2017. This study adopted a qualitative approach that involved eight non-participant observations conducted using a checklist (Adapted and Modified from: Tools to Assess Family Planning Counselling: Observation and Interview) and 38 in-depth interviews. The interviewees consisted of 11 T2DM women, seven spouses and 20 healthcare providers. Purposive sampling was applied and the interviews were conducted by the researcher in either the English or the Malay language and by following tailor-made semi-structured interview guides that covered topics such as types of methods preferred and perceptions on family planning utilization and services at primary healthcare services. All interviews were recorded, transcribed and analysed by using thematic analysis. Data management was performed by using NVIVO version 11 software. Several strategies were adopted to enhance iv the quality of data analysis, e.g. triangulation (data, method and investigator), peer review and feedback from presentations at district meetings and conferences. Thematic analysis was used to explore the findings from the interviews which were categorized into 14 themes at three Socio-ecological model levels, the individual, interpersonal and organizational. Underutilization of family planning was influenced by personal preferences and goals, and lack of healthcare providers’ expertise delivering family planning services. This, followed by information-seeking related to family planning methods from entrusted spouse, family members, friends, and healthcare providers to enable decision-making related to utilization of family planning methods. The study also elicited suggestions from the interviewed healthcare providers regarding ways in which family planning services might be improved, from which seven themes emerged. Improving the current services in primary healthcare facilities and increasing knowledge among the healthcare providers are among strategies suggested by the providers to increase family planning utilization. The findings of this study suggest that an element of uniqueness exists because individual experiences with regard to the side effects of family planning methods and complications are different for each woman. This study also highlighted the importance of spouses’ role especially in family planning utilization decision-making. They also underline the importance of the role of healthcare providers and the current healthcare system in providing family planning services within primary healthcare facilities. In addition, the findings imply that T2DM women should be encouraged to share their concerns with their healthcare providers. Simultaneously, healthcare providers should be equipped with adequate information and skills to provide suitable family planning methods to diabetic women. This would reduce unnecessary pregnancy-related complications being experienced by T2DM women. T2DM women should be encouraged to share their concern on family planning methods with their healthcare providers. Simultaneously, healthcare providers could encourage patients to verify any new v information received from sources other than medical experts. The findings of this study are believed to have broader applicability to women with other pre-existing medical illnesses that are managed at primary healthcare facilities.